2000
DOI: 10.1063/1.1323535
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dislocation mechanism for melting of elements: Pressure dependence

Abstract: In the framework of melting as a dislocation-mediated phase transition we derive an equation for the pressure dependence of the melting temperatures of the elements valid up to pressures of order their ambient bulk moduli. Melting curves are calculated for Al, Mg, Ni, Pb, the iron group (Fe, Ru, Os), the chromium group (Cr, Mo, W), the copper group (Cu, Ag, Au), noble gases (Ne, Ar, Kr, Xe, Rn), and six actinides (Am, Cm, Np, Pa, Th, U). These calculated melting curves are in good agreement with existing data.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 55 publications
2
54
0
Order By: Relevance
“…Finally, we note that our model for γ can be used to calculate shear moduli along the solidus using Eq. (8) and the formula G(ρ, T m (ρ))/(ρ · T m (ρ)) = constant [43]. Table 1 vs. the experimental data [40] and the results of calculations [44] (larger points).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that our model for γ can be used to calculate shear moduli along the solidus using Eq. (8) and the formula G(ρ, T m (ρ))/(ρ · T m (ρ)) = constant [43]. Table 1 vs. the experimental data [40] and the results of calculations [44] (larger points).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the parameters used in the melting temperature models of copper. Figure 3 shows a comparison of the two melting temperature models along with experimental data from Burakovsky et al (2000a) (shown as open circles). An initial density ρ 0 of 8930 kg/m 3 has been used in the model calculations.…”
Section: The Burakovsky-preston-silbar (Bps) Melt Modelmentioning
confidence: 99%
“…The remaining parameters for the BPS model are from Burakovsky and Preston (2000) and Burakovsky et al (2000b). Burakovsky et al (2000a). The original sources of the experimental data can be found in the above citation.…”
Section: Mts Shear Modulus Modelmentioning
confidence: 99%
See 2 more Smart Citations